2011
DOI: 10.1007/s00109-011-0806-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcript signature predicts tissue NK cell content and defines renal cell carcinoma subgroups independent of TNM staging

Abstract: Clear cell renal cell carcinoma (ccRCC) is an aggressive and difficult to manage cancer. Immunotherapy has the potential to induce long-lasting regression in a small group of patients. However, severe side effects limit broad application which highlights the need for a marker to distinguish responder from nonresponder. TNMG staging, referring to tumor size, lymph node involvement, presence of metastasis, and grade of tumor differentiation, represents an important prognostic system but is not useful for predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 32 publications
6
71
0
Order By: Relevance
“…Natural killer (NK) cells play an important role as first-line defenders in the host response to tumors and infections, in transplant rejection, and the development of tolerance (5). The presence of intratumoral NK in RCC correlates with improved patient survival (6). Recent studies suggest that immunotherapy may be an effective approach for patients with RCC (7), and emerging strategies are currently under investigation based on adoptive transfer of T or NK cells (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Natural killer (NK) cells play an important role as first-line defenders in the host response to tumors and infections, in transplant rejection, and the development of tolerance (5). The presence of intratumoral NK in RCC correlates with improved patient survival (6). Recent studies suggest that immunotherapy may be an effective approach for patients with RCC (7), and emerging strategies are currently under investigation based on adoptive transfer of T or NK cells (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the presence of immature NK cells in 2C 2 leads to the development of de novo genitourinary tumors. Further investigations with larger numbers of patients are required to confirm these hypotheses; nonetheless, the findings that Marc-Olivier Bitker, 3 Alain Chapelier, 4 Jean-Paul Couetil, 2 Philippe Dartevelle, 5 Michel Delahousse, 4 Philippe Deleuze, 6 Bertrand Dousset, 7 Denis Glotz, 1 Laurent Hannoun, 3 Philippe Lang, 2 Francoise Le Pimpec Barthes, 8 Patrick Nataf, 9 Patrick Niaudet, 10 Jean-Jacques Patard, 11 Alain Pavie, 3 Eric Rondeau, 12 Didier Samuel, 13 Emmanuel Tiret, 14 Dominique Valla, 15 Coordinator for epidemiology: Caroline Besson 11 Coordinators for immunology: Patrice Debré, 16 Antoine Toubert, 1 and Vincent Vieillard 16 Coordinators for pharmacogenetics: Laurent Puig, 8 Laurent Thervet …”
Section: Discussionmentioning
confidence: 99%
“…An 11-y generalpopulation follow-up study showed that high NK cytotoxic activity is associated with reduced risk of cancer (7). In addition, NK cell infiltration into tumor tissues is associated with better disease prognosis in non-small-cell lung carcinoma (8), renal cell carcinoma (9), and colorectal carcinoma (10). NK cells are heterogeneous and differ in their proliferative potential, homing characteristics, functional capacities, and responses to different cytokines.…”
mentioning
confidence: 99%
“…Poor Poor (Dannenmann et al, 2013;Komohara et al, 2011;Xu et al, 2014) Good (Donskov, 2007;Eckl et al, 2012) Prostatic adenocarcinoma…”
Section: )mentioning
confidence: 98%